Semiconductor/Polymer/Semiconductor double junction thin film for photovoltaic application - Al-Bat’hi, Souad (2011)
Recent advances in photovoltaic technology have made materials (other than silicon) in combination attractive for the design of solar cells. Designers layer semiconductor materials with differing band gap energies to result in higher conversion efficiencies. In this work multijunction cells consist of multiple thin films produced using electrochemical deposition technique on ITO glass substrates have been fabricated and characterized. Each cell configured as, ZnSe/polymer/ZnO and the polymer in this work is a blend of 50 wt% Chitosan and 50 wt% polyethylene oxide (PEO). To provide I-/I3- redox couple, ammonium iodide NH4I and some iodine crystals were added to the polymer blend solution. The polymer electrolyte film that showed highest room temperature ionic conductivity of 1.18 x 10-5 S cm-1 was sandwiched between the ZnSe and ZnO semiconductors. The I–V characteristics for the determination of open circuit voltage, Voc and short-circuit current, Isc were carried out in the dark and under illumination. The cell was illuminated with a GE EDYSON neon lamp and the effective area was 1.0 cm2.